Horse - Clutton-Brock, Juliet (Dorling Kindersley London, 2000)
A photo essay introducing members of the horse family, their evolution, behavior, importance, history, breeding, and taining. Includes major international breeds of domestic horses.
Includes index
1250L
Keywords: Horses -- Juvenile Literature; Equus -- Juvenile Literature; Horse breeds -- Juvenile Literature; Equidae; Horses; Horse breeds